Ordböcker på Internet och Internet som ordbok - Törnqvist, Lars (Nordiske Studier i Leksikografi, 2010)
This paper gives an overview of present trends in Internet lexicography. Some methods of using web dictionaries and other websites for lexicographic purposes are presented. It ends up in a question: Are dictionaries really needed in the future?